Pengaruh Penggunaan LKPD Berbasis Model Pembelajaran Creative Problem Solving Terhadap Kompetensi Fisika Peserta Didik Kelas XI SMAN 1 Pariaman - Ricca Tiara; Ramli Ramli; Masril Masril (Universitas Negeri Padang, 2018)
One of the efforts to improve the quality of physics learning in grade XI SMAN 1 Pariaman is to use LKPD based on creative problem solving learning model. It is expected that this LKPD can contribute in the achievment of students physics competence. This study aims to see how much influence the use of LKPD based creative problem solving learning model of students of class XI SMAN 1 Pariaman. This research is classified into Pre-Experimental Design with One Shot Case Study design study. The populations of this research are students of class XI SMA N 1 Pariaman with regestered semester II year 2016/2017. Sampling is done by purposive sampling technique followed by randomly select to determine the sample class. The data obtained in this research include physics competence data of learnes on attitude, knowledge, and skill aspect.Competence attitude is assessment observation sheet of student attitude. Assessment of knowledge competence is trough obtained written test in the form of multiple choice and assessment of learning process using steps of creative problem solving model.Skill competence is assessed trough performance technique with instrument in scoring rubric. The data of knowledge and skill competence are analyzed using simple linear regression test, linearity test and test of two variable relationship at real level 0,05. The result of the competence analysis of the attitude of the students shows the increase and decrease every week.Meanwhile, the result of knowledge and skills competence analysis shows that there is a significant influence on the use of LKPD based on creative problem solving model with a contribution of 17,64% for knowledge competence and 15,21% for skill competence.